Ant-colony and nature-inspired heuristic models for NOMA systems: a review - Law Poh Liyn; Hadhrami Ab. Ghani; Farah Najwa Roslim; Nur Asyiqin Amir Hamzah; Saeed Mohammed Abdulghani Mohammed; Nor Hidayati Abdul Aziz; Azlan Abd. Aziz; Tan Kim Geok; Azizul Azizan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The increasing computational complexity in scheduling the large number of users for non-orthogonal multiple access (NOMA) system and future cellular networks lead to the need for scheduling models with relatively lower computational complexity such as heuristic models. The main objective of this paper is to conduct a concise study on ant-colony optimization (ACO) methods and potential nature-inspired heuristic models for NOMA implementation in future high-speed networks. The issues, challenges and future work of ACO and other related heuristic models in NOMA are concisely reviewed. The throughput result of the proposed ACO method is observed to be close to the maximum theoretical value and stands 44% higher than that of the existing method. This result demonstrates the effectiveness of ACO implementation for NOMA user scheduling and grouping.